Distribution of small proteoglycans and glycosaminoglycans in humerus-related articular cartilage of chickens - E.D. Rodrigues; E.R. Pimentel; P.A.S. Mourão; L. Gomes (Brazilian Journal of Medical and Biological Research, 2005)
The expression of components present in the cartilaginous extracellular matrix is related to development, gender, and genotype, as well as to the biomechanical properties of each type of cartilage. In the present study, we analyzed small proteoglycans and glycosaminoglycans present in different cartilages of the chicken wing after extraction with guanidine hydrochloride or papain. Quantitative analysis of glycosaminoglycans showed a larger amount in humeral cartilage (around 200 mg/g tissue) than in articular cartilage of the radius and ulna, with 138 and 80 mg/g tissue, respectively. Non-collagenous proteins isolated were predominantly from cartilage in the proximal regions of the humerus and radius. D4 fractions obtained by ultracentrifugation were separated by DEAE-Sephacel and Octyl-Sepharose chromatography and analyzed by SDS-PAGE. Two bands of 57 and 70-90 kDa were observed for all samples treated with ß-mercaptoethanol. Immunoblotting of these proteins was positive for the small proteoglycans fibromodulin and decorin, respectively. Apparently, the 57-kDa protein is present in macromolecular complexes of 160 and 200 kDa. Chondroitin sulfate was detected in all regions. HPLC analysis of the products formed by chondroitinase AC and ABC digestion mainly revealed ß-D-glucuronic acid and N-acetyl ß-D-galactosamine residues. The 4-sulfation/6-sulfation ratio was close to 3, except for the proximal cartilage of the radius (2.5). These results suggest functional differences between the scapula-humerus, humerus-ulna, and humerus-radius joints of the chicken wing. This study contributes to the understanding of the physiology of cartilage and joints of birds under different types of mechanical stress.